The Truth of the Hadith about the Reasons for the Revelation of Surah Al-Kāfirūn and Its Effect on Religious Tolerance - Rohmansyah Rohmansyah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Hadith’s authenticity on crucial things, such as tolerance in Surah Al-Kāfirūn, must be studied. This paper aims to reveal and prove the status of the hadith as evidence of the revelation of Surah Al-Kāfirūn, associated with religious tolerance. This study belongs to library research implementing a descriptive-analytic approach and a theoretical framework of the Sociology of Knowledge by Peter L Berger and Thomas Lukmann. The results unveiled that the hadith concerning the revelation of Surah Al-Kāfirūn cannot be used as evidence because it was daif and mawquf. However, the tacitan of the hadith did not weaken the validity of the surah, of which the status is the word of God, which is qaṭ’ī. Therefore, Al-Kāfirūn’s correlation with religious tolerance remains valid as long as it pays attention to the determined limits. Mutual respect, assistance, and cooperation among religious people of different beliefs, and things unrelated to ideological aspects such as aqidah, worship, and sharia must be considered.The descent of surat al-Kāfirun exerts a considerable influence on the religiousness of the people. Every human being is free to choose his religion according to his beliefs and their own beliefs. But especially Muslims have rules that stick to their religion, as well as non-Muslims. Mereka is free to perform worship according to his understanding and belief. Surat al-Kāfirūn in addition to teaching plurality in religion also teaches the attitude of maintaining unity and unity of the people, reducing hostility and eliminating violence and panatic against other groups. The majesty of surat al-Kāfirūn became a way out of the problem of conflict between religious people since its descent until now so that between religious people live get along well and don't bother each other.